Pemetaan Zona Rawan Banjir di Kabupaten Luwu Utara Menggunakan Metode Analytic Hierarchy Process (AHP) yang Terintegrasi dalam Sistem Informasi Geografis (SIG) - Subaer Subaer; Pariabti Palloan; Tiardo Simangunsong (Universitas Andalas, 2024)
Research has been conducted to map flood-prone zones in North Luwu Regency by considering rainfall parameters, soil type, slope, land use, geology, drainage density, road density distance and elevation. The method used in this research is the Analytical Hierarchy Process (AHP) method integrated with Geographic Information Systems (GIS). The purpose of this research is to determine how much each parameter contributes to flood risk and visualize the results in the form of flood-prone maps. The results in this study show that rainfall has the biggest cause of flood risk at 0.30, followed by slope 0.20, land use 0.13, elevation at 0.12, drainage density 0.09, geology 0.07, soil type 0.05, and distance between roads at 0.04. All parameters that have been analyzed, then weighted overlay into a flood-prone map. The mapping results show that North Luwu Regency has a moderate level of flood risk, with an area coverage of 3.813 km2 or 50,78% of the total area. As for the vulnerable level category, it covers an area of 17,48 km2 or 23,28%, and for the moderately vulnerable zone level category it covers an area of 1.939 km2 or 25,82% of the total area.